Spis treści [Knowledge and Digitalisation Against Corruption and Fraud / ed. P. Luty, N. Versal, P. Semerád. - Wroclaw, 2024] - Luty, Piotr. Redakcja; Versal, Nataliia. Redakcja; Semerád, Pavel. Redakcja (Publishing House of Wroclaw University of Economics and Business, 2024)
[The present book is the first of three monographs describing the research results on combating corruption and fraud. The publication is divided into seven chapters. The first chapter focuses on trends in corruption indices in Ukraine and the Czech Republic and assesses policy responses to corruption. The second one describes digital transformation in combating welfare fraud. In the third chapter the authors cover an important issue related to compliance with the principles of transparency in the public procurement process. The fourth chapter deals with fighting the shadow economy by introducing new forms of employment. The fifth chapter examines the development of payment systems in Eastern Europe over the last decade and the opportunity for further improvement through adopting new digital payment technologies. The sixth chapter deals with electronic evidence of sales in the Czech Republic. The last, seventh chapter analyses the instruments implemented in Poland to minimise the VAT gap.] z zapowiedzi
s. 104
Keywords: corruption; welfare fraud; VAT gap; payment systems; shadow economy